Isotopic ratios for subglacial precipitates from East Antarctica - Blackburn, Terrence (IEDA: EarthChem Library, 2020)
Abstract: U-Series composition of subglacial precipitates from East Antarctica. Samples are from Elephant Moraine and the Pensacola Mountains. They are chemical precipitates of either entirely calcite or opal and calcite. Other Description: Blackburn, T., Edwards, G., Tulaczyk, S., Scudder, M., Piccione, G., McLean, N.M., Hallet, B., Zachos, J., Cheney, B., Babbe, J., Retreat of the East Antarctic Ice Sheet in response to 1-2 °C of warming. Nature (accepted)